Preliminary Observations on Field Trial of Root Trainer Raised Seedlings - Gera, Mohit; Ginwal, H. S. (Indian Forester, 2002)
The interest to produce quality seedlings is gaining momentum in recent years. Modern nursery methods such as root trainers, improved polythene bag planting systems are being introduced. In order to compare the different seedling production systems, seedlings of three different tree species namely Acacia nilotica, Dalbergia sissoo and Albizia procera were raised through seven different methods including root trainers. The seedlings were assessed for quality parameters, viz., sturdiness, number of nodules, root/shoot ratio and ratio of fibrous to total root biomass, before field planting. Root trainer raised seedlings were found to be better in sturdiness whereas nodulation was observation to be better in seedlings raised on MAl beds for all species. Maximum root/shoot ratio was observed in root trainers raised seedlings whereas no distinct differences were observed in the ratio of fibrous to total root biomass. The field assessment of the seedlings after one and a half year of plantiug revealed that root trainer raised seedlings registered maximum growth increment for all species except collar diameter in case of Dalbergia sissoo.